A new look at the safety and tolerability of prostaglandin analogue eyedrops in glaucoma and ocular hypertension. Issue 4 (3rd April 2022) - Katsanos, Andreas; Riva, Ivano; Bozkurt, Banu; Holló, Gábor; Quaranta, Luciano; Oddone, Francesco; Irkec, Murat; Dutton, Gordon N.; Konstas, Anastasios G.
ABSTRACT: Introduction: In the last 25 years, topical prostaglandin analogues (PGAs) have emerged to become first line and first choice therapeutic options in the management of glaucoma and ocular hypertension (OHT). Although the short-term efficacy and safety of PGAs has been extensively investigated, less is known about their long term safety and tolerability. This gap in current knowledge is clinically relevant, because treatment-related adverse events and long-term tolerability issues are key determinants of the overall success of long-term therapy and the final outcome of a lifelong, symptomless disease like glaucoma. Areas covered: We include selected evidence pertaining to the safety and tolerability of available and emerging PGA formulations. We also outline PGA formulations with different concentrations of the active ingredient, different preservatives, and preservative-free (PF) options. Expert opinion: Undoubtedly PGAs will continue to play a major role in the medical therapy of glaucoma and OHT. Despite extensive literature and prolonged clinical experience with these agents worldwide, a number of areas that warrant further research have been identified in the present review. Recently launched novel PGAs, or those still in development offer new opportunities and future challenges.